STRATEGI PENGEMBANGAN UMKM RUMAH JAHIT F-Ros COLLECTION TERHADAP KEBIJAKAN DINAS KOPERASI, PERINDUSTRIAN DAN PERDAGANGAN (DISKOPERINDAG) KABUPATEN SITUBONDO - Pradani, Rizki Febri Eka; Hasanah, Dini Washilatul; Fitriyah, Mariyatul; Hakiki, Nawal Firkah; Sa’adah, Farihatus (Fakultas Ekonomi dan Bisnis, 2025)
The journey of Micro, Small and Medium Enterprises since 2008 has experienced ups and downs regarding their role and function in the sustainability of the economic system in Indonesia. As the main foundation that supports the Indonesian economy, Micro, Small and Medium Enterprises are required to be more independent by developing human resources, developing product varieties and marketing systems, as is done by the F-Ros Collection sewing house which operates in the service sector. The role of bureaucratic policy that handles the problems of Small and Medium Enterprises is that of the Cooperation and Trade Department as a forum for Micro, Small and Medium Enterprises actors to develop and facilitate the existence and sustainability of Micro, Small and Medium Enterprises. However, in practice there are often problems between existing policies and their proper roles. This is often inversely proportional to the minimal budget allocated for developing Micro, Small and Medium Enterprises. Therefore, there are still many disparities which are a problem for Micro, Small and Medium Enterprises actors in getting attention from the appointed bureaucracy. The uneven implementation of existing work programs will have a less than optimal impact on the performance and role of the bureaucracy. Micro, Small and Medium Enterprises actors need to be aware of these things in order to be independent and always think positively about the cooperative, industry and trade services because this institution only implements work programs from the regional government.